2017
DOI: 10.1590/s0004-2803.2017v54n1-11
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between vitamin D and liver fibrosis in patients with chronic hepatitis C?

Abstract: BACKGROUND Vitamin D is known for its immunomodulatory, anti-inflammatory and antifibrotic properties, which are quite relevant in the pathogenesis and treatment of many causes of chronic liver disease. OBJECTIVE This study aimed to evaluate the association between serum vitamin D levels and the histopathological findings in patients with chronic hepatitis C virus infection. METHODS Cross-sectional study composed of patients with chronic hepatitis C. All patients underwent vitamin D 25 dosage and anthropomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…For example, treatment-naive Chinese HCV patients failed to show any correlation between serum levels of 25(OH)D 3 and 24,25(OH) 2 D 3 and liver fibrosis [54]. Oliveira et al and Esmat et al also reported no significant association between VD serum levels and inflammatory activity or the degree of liver fibrosis [55,59]. Another clinical study also suggested that VD deficiency was not responsible for poor virological characteristics in HCV patients [36].…”
Section: Effect Of Vd On Hcv Pathogenesismentioning
confidence: 98%
“…For example, treatment-naive Chinese HCV patients failed to show any correlation between serum levels of 25(OH)D 3 and 24,25(OH) 2 D 3 and liver fibrosis [54]. Oliveira et al and Esmat et al also reported no significant association between VD serum levels and inflammatory activity or the degree of liver fibrosis [55,59]. Another clinical study also suggested that VD deficiency was not responsible for poor virological characteristics in HCV patients [36].…”
Section: Effect Of Vd On Hcv Pathogenesismentioning
confidence: 98%
“…According to Berkan-Kawińska et al [ 121 ], even though those with chronic hepatitis C or chronic hepatitis B may have insufficient levels of 25(OH)D, there is no evidence that these deficiencies lead to a worse prognosis for patients. Additionally, studies have shown no link between vitamin D levels in blood and liver fibrosis [ 122 , 123 ] or poor responses to anti-viral treatments for HCV infection [ 124 , 125 , 126 , 127 , 128 , 129 ]. It is worth noting that the levels of 25(OH)D3 did not seem to affect the effectiveness of the treatment in the African-American population [ 129 ].…”
Section: Controversy In Roles That Vitamin D May Play In Viral Infectionmentioning
confidence: 99%
“…За даними літератури відомо, що поширеність недостатності вітаміну D серед хворих на ХГС становить від 39,2% до 71%, а серед хворих на ХП -від 22% до 86,6% [7,8]. Bakstedt et al, Oliveira et al повідомляли, що сироватковий рівень вітаміну D може впливати на природній перебіг ХГС, а саме -на інтенсивність запалення та фіброгенезу [9,10]. Розвиток дефіциту вітаміну D при ХГС коморбідному з ХП пов'язаний зі зниженням його кишкової абсорбції, порушенням зв'язку з транспортними білками, порушенням гідроксилювання вітаміну D в гепатоцитах, результатом чого є зниження кількості його активних метаболічних форм [7].…”
Section: вступunclassified